PROFIL GAYA BELAJAR SISWA MELALUI PENDEKATAN KONSTRUKTIVISME DI SMA ANTARTIKA SIDOARJO - Nerva Nur Opticia (Buana Matematika : Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2016)
Understanding of mathematical concepts can be controlled well by the students if teachers can make students tend to be active pembelajaran.Untuk approach is needed to make students more active role in learning. One way that could condition the students play an active role in learning is the constructivism approach. This approach begins with giving problems to the students who ultimately students are expected to find their own way of solving the problem. In order for this study could be run better then the teacher should know the learning styles of each Shiva in order to adapt the way of good teaching. Observed learning styles are visual, auditory, and kinesthetic. The data source of this research in X Mipa 5 SMA Antartika Sidoarjo. Of the class was given a questionnaire about learning styles. Then the results of the questionnaire is reduced so that the two subjects are drawn from every learning style. Having drawn six subjects, administered tests problem solving with the criteria for having written a neat, use of symbols in the plant concept, task writing / composing, sensitivity to issues of artistic and understand about the form of the writing / reading From the results of these tests chrosscheked with interview , From the analysis of the test has been obtained, is obtained as follows. Profiles visual learning style has characteristics include in Lesson prefer casual, like raised his voice while reading, more like a lot of theory in practice, dislikes memorize and like math but weak in the count. Profile auditory learning style has characteristics include the time work on the problems less conscientious, like move their lips while reading, more like learning groups, dislike to memorize, like mathematics. Profile kinesthetic learning style has characteristics include the time learning like more prektek, sometimes like moving his lips while reading, more like learning groups, dislike to memorize, dislike math. Keywords: Learning Styles, Constructivist Approach.